Biogas Utilization Using Fish Waste with Constant Volume of Inoculum Cow-Dung - Zamazal, Petr; Winaya, I Nyoman Suprapta; Astawa, Ketut (International Journal of Engineering and Emerging Technology, 2017)
This research used fish waste as a raw material and inoculum cow-dung as a starter to produce biogas. It was calculated the weight of total solid and volatile total solid for the right amount of substrate to be incorporate into the digesters. The variation of 5g, 6g, 7g, 8g, 9g and 10g of volatile total solid was mixed with the inoculum cow-dung 100ml and water as the rest, which was filled up to 300ml of the total volume of slurry. Two digesters with amount of 100ml inoculum cow-dung and 200ml water were used as the comparison. This research was conducted for 30 days and it was measuring pressure in digesters, temperature and pH, which was conditioned once a week with NaOH or H2SO4. The best result can be seen in the variation of 5g fish waste as a substrate. The volume in the digester is 93.93ml/gVS with percentage levels of CH4 by 51% and CO2 by 47%.